The impact and cost‐effectiveness of community‐based HIV self‐testing in sub‐Saharan Africa: a health economic and modelling analysis. (25th March 2019) - Cambiano, Valentina; Johnson, Cheryl C; Hatzold, Karin; Terris‐Prestholt, Fern; Maheswaran, Hendy; Thirumurthy, Harsha; Figueroa, Carmen; Cowan, Frances M; Sibanda, Euphemia L; Ncube, Getrude; Revill, Paul; Baggaley, Rachel C; et al.
Abstract: Introduction: The prevalence of undiagnosed HIV is declining in Africa, and various HIV testing approaches are finding lower positivity rates. In this context, the epidemiological impact and cost‐effectiveness of community‐based HIV self‐testing (CB‐HIVST) is unclear. We aimed to assess this in different sub‐populations and across scenarios characterized by different adult HIV prevalence and antiretroviral treatment programmes in sub‐Saharan Africa. Methods: The synthesis model was used to address this aim. Three sub‐populations were considered for CB‐HIVST: (i) women having transactional sex (WTS); (ii) young people (15 to 24 years); and (iii) adult men (25 to 49 years). We assumed uptake of CB‐HIVST similar to that reported in epidemiological studies (base case), or assumed people use CB‐HIVST only if exposed to risk (condomless sex) since last HIV test. We also considered a five‐year time‐limited CB‐HIVST programme. Cost‐effectiveness was defined by an incremental cost‐effectiveness ratio (ICER; cost‐per‐disability‐adjusted life‐year (DALY) averted) below US$500 over a time horizon of 50 years. The efficiency of targeted CB‐HIVST was evaluated using the number of additional tests per infection or death averted. Results: In the base case, targeting adult men with CB‐HIVST offered the greatest impact, averting 1500 HIV infections and 520 deaths per year in the context of a simulated country with nine million adults, and impact could be enhanced by linkage to voluntary medical male circumcision (VMMC). However, the approach was only cost‐effective if the programme was limited to five years or the undiagnosed prevalence was above 3%. CB‐HIVST to WTS was the most cost‐effective. The main drivers of cost‐effectiveness were the cost of CB‐HIVST and the prevalence of undiagnosed HIV. All other CB‐HIVST scenarios had an ICER above US$500 per DALY averted. Conclusions: CB‐HIVST showed an important epidemiological impact. To maximize population health within a fixed budget, CB‐HIVST needs to be targeted on the basis of the prevalence of undiagnosed HIV, sub‐population and the overall costs of delivering this testing modality. Linkage to VMMC enhances its cost‐effectiveness.